Effect of boron nitride as a nucleating agent on the crystallization of bacterial poly(3‐hydroxybutyrate). Issue 5 (27th June 2012) - Puente, Jorge Arturo Soto; Esposito, Antonella; Chivrac, Frédéric; Dargent, Eric
Abstract Different concentrations of boron nitride (BN) (0.2–0.8 wt %) are added to poly (3‐hydroxybutyrate) (PHB) as a nucleating agent. Polarized Optical Microscopy (POM) coupled to Differential Scanning Calorimetry (DSC) allow to monitor the isothermal and nonisothermal crystallization of neat and nucleated PHBs. It is found that the addition of BN to PHB modifies the mechanisms of crystallization without changing the crystallinity degree. DSC can replace POM whenever POM does not allow to estimate the spherulites growth rate. The Hoffman‐Lauritzen theory is used to explain the role of BN. The nucleating agent allows polymer crystallization at lower supercooling degrees. The regime II of crystallization is observed for nucleated PHBs. A modification of the coupling effect between the amorphous and the crystalline phases is evidenced. It is shown that a concentration of 0.2 wt % BN is sufficient to decrease the glass transition temperature and modify the crystallization mechanisms of PHB. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013